IMPLEMENTASI KURIKULUM BAHASA INDONESIA ANTARA HARAPAN DAN KENYATAAN - Nursalim Nursalim (Lembaga penelitian dan pengabdian kepada Masyarakat, 2011)
Abstraction: This Study copes to open Big Outline implementations of Program Instruction (GBPP) Indonesian Subject at Set Mount Curriculum Of Education (KTSP), Elementary School (SDN) in school activity (KBM) in the class. The purpose of this Study is to: (1) knowing whether teacher fulfill instruction procedure